The development of concepts in science: A survey of junior secondary pupils in Guyana - Adey, Philip S. (Ministry of Education, 1976)
Two class tasks were administered to 11 to14-year-old pupils from five schools, in order to assess typical levels of cognitive development. Results are shown for secondary and all-age pupils, first by age and then by school year. Comparison between selective and non-selective schools shows that the levels of development in the former were higher than in the latter. In the selective secondary schools there appeared to be a quite sudden growth in the proportion of formal operational thinkers in the fourth year. In the all-age schools, some 30 percent of pupils in their first year were pre-operational. There appeared to be some difference in the rate at which boys and girls in secondary schools achieved the concepts investigated and three hypotheses are proposed. An analysis of the conceptual demands of the West Indian Science Curriculum (WISC) indicates that much of the curriculum makes demands at the late concrete operational level. This can only be met by 50 percent of the first-year pupils in secondary schools and by not more than 30 percent of pupils in the all-age schools
Keywords: West Indian Science Curriculum